Early pathogenesis profiles across SARS-CoV-2 variants in K18-hACE2 mice revealed differential triggers of lung damages - Aw, Zhen Qin; Mok, Chee Keng; Wong, Yi Hao; Chen, Huixin; Mak, Tze Minn; Lin, Raymond T. P.; Lye, David Chien; Tan, Kai Sen; Chu, Justin Jang Hann (Frontiers in Immunology, 2022)
The on-going COVID-19 pandemic has given rise to SARS-CoV-2 clades and variants with differing levels of symptoms and severity. To this end, we aim to systematically elucidate the changes in the pathogenesis as SARS-CoV-2 evolved from ancestral to the recent Omicron VOC, on their mechanisms (e.g. cytokine storm) resulting in tissue damage, using the established K18-hACE2 murine model. We reported that among the SARS-CoV-2 viruses tested, infection profiles were initially similar between viruses from early clades but started to differ greatly starting from VOC Delta, where the trend continues in Omicron. VOCs Delta and Omicron both accumulated a significant number of mutations, and when compared to VOCs Alpha, Beta, and earlier predecessors, showed reduced neurotropism and less apparent gene expression in cytokine storm associated pathways. They were shown to leverage on other pathways to cause tissue damage (or lack of in the case of Omicron). Our study highlighted the importance of elucidating the response profiles of individual SARS-CoV-2 iterations, as their propensity of severe infection via pathways like cytokine storm changes as more variant evolves. This will then affect the overall threat assessment of each variant as well as the use of immunomodulatory treatments as management of severe infections of each variant.